Acute Changes in Postural Control after Soccer Heading - Haran, F. J.; Tierney, R.; Wright, W. G.; Keshner, E.; Silter, M. (International Journal of Sports Medicine, 2013)
This study intended to determine if an acute bout of soccer heading alters postural control and pronounced self-reported symptoms of cerebral concussion. Collegiate soccer players were randomly assigned to one of 2 groups. Each participant completed a baseline postural control assessment prior to heading. Participants either simulated (control group; CG) or performed (experimental group; EG) 10 headers at 11.2 m/s in 10 min. The postural assessment was repeated post heading at hrs 1, 24, and 48. The postural control parameter assessed was the root mean square (RMS) of the center of mass (COM). COM RMS were calculated for the anterior-posterior (AP) and medial-lateral (ML) time series. Compared to the CG, for the AP and ML time series COM RMS values were significantly higher in the EG at hr 24 (p <0.05). An acute bout of heading results in quantifiable alterations in postural control that are detectable 24 h post heading and dissipate within an additional 24 h. The significant findings may be due to the dynamic postural control assessment that incorporated robust discordant environmental conditions.
Keywords: concussion; MTBI; balance; stability; virtual environment